DAYA DUKUNG PARIWISATA DI DESA PENYANGGA TAMAN NASIONAL WAY KAMBAS PROVINSI LAMPUNG - Gilang Fahreza; Mezi Julian; Donna Ekawaty (Journal of Innovation Research and Knowledge, 2025)
Way Kambas National Park (TNWK) in Lampung province is one of dozens of national parks in Indonesia. As the largest elephant conservation center in Indonesia, TNWK is a very unique destination and is in particular demand by Lampung residents. Elephant agility attractions, elephant riding, elephant painting, elephant playing ball are tourist attractions offered by TNWK. However, after conducting a review and evaluation in 2019, the attractions offered by TNWK were considered not to be on the side of conservation principles because behind the cute and adorable elephant attractions there was a very hard training process. Therefore, the TNWK Center plans to change the tourism style in TNWK which was previously massive tourism to an alternative tourism based on education and involving local residents as a driving force for tourism. This change in tourism style of course requires a lot of studies to mitigate the readiness of the TNWK and the residents of the buffer villages who will later become the driving force of tourism in TNWK. One of them is to study the carrying capacity of tourism in 4 buffer villages (Labuhan Ratu 6, 7, 9 and Braja Harjosari Village) which are the gateways of TNWK. This research is a qualitative research that collects data using observation, documentation, interview, and library research methods. This research focuses on 3 aspects of tourism carrying capacity according to the World Tourism Organization (UNWTO), namely physical-ecological aspects; socio-demographic, economic-political. As a result of this study, the current carrying capacity of TNWK and 4 buffer villages is 75.2% physical-ecological aspects, 90.4% socio-demographic aspects, and 95% economic-political aspects. The indicators of the carrying capacity aspect that must receive more attention from TNWK and the 4 buffer villages are waste separation and management management which only meets 33.33%, renewable energy use only meets 25%, and companies with low energy consumption systems only meet 25%.